Main factors that influence the process of translating texts from English into Spanish of students registered in translation I at the Foreign Language department, University of El Salvador, semester I-2018 - González Sosa, José Edgardo
The following research paper work describes the “Main factors that influence the process of translating texts from English into Spanish of students registered in Translation I at the Foreign Language Department, University of El Salvador, semester I-2018”. This research is developed with the help of many important components such as instruments, resources and contribution from the population that was given the opportunity to participate and get involved in it with the objective of gathering information and so take an active role in the process of confirming certain hypotheses stated on the research paper. The same one intends to develop the following research question: What are the predominant factors that influence the process of translating texts from English into Spanish in students of Translation I at the FLD, University of El Salvador, semester I-2018? which has been set up with the purpose of understanding the difficulties encountered by students at the time of translating a specific document.